FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI WILAYAH PERKOTAAN INDONESIA BAGIAN TIMUR: ANALISIS DATA RISKESDAS 2018 - Suariyani, Ni Luh Putu; Cahyani, Ida Ayu Made Gia (ARCHIVE OF COMMUNITY HEALTH, 2024)
Hypertension is a disease whose incidence continues to increase both in the world and in Indonesia. The highest prevalence of hypertension in Indonesia occurs in urban areas. This can be influenced by the lifestyle of urban communities such as risky consumption patterns and lack of physical activity which makes urban communities more at risk of developing hypertension. The purpose of this study is to determine the factors associated with hypertension in the urban areas of Eastern Indonesia. This research is an analytic observational study with a cross sectional design. The sample in this study was 38,271 respondents who were individuals aged ? 18 years living in urban areas in eastern Indonesia (Bali, Nusa Tenggara, Sulawesi, Maluku, Papua) who were respondents to the 2018 Riskesdas and met the sample selection criteria. This study used probability sampling with Two Stage Sampling which is a technique in determining the sample used in Riskesdas 2018. Data analysis was carried out namely univariate, bivariate with simple logistic regression analysis and multivariate with multiple logistic regression analysis. The results of this study, namely the percentage of hypertension reached 16.83%. Hypertension related to obesity (OR 1.81; 95% CI 1.62-1.92), history of diabetes (OR 1.81; 95% CI 1.60-2.27), physical activity (OR 1.14; 95% CI 1.01-1.31), and smoking habits (OR 1.46; 95% CI 1.26-1.52). The conclusion of the research results are sociodemographic factors, physical factors and medical history as well as lifestyle factors that influence the occurrence of hypertension, namely age, education, employment, obesity, history of diabetes, physical activity, smoking habits, and consumption of salty foods. Keywords: Hypertension, Urban, Eastern Indonesia